Immuno-Ultrastructural Localization and Putative Multiplication Sites of Huanglongbing Bacterium in Asian Citrus Psyllid Diaphorina citri - Ammar, El-Desouky (Insects, 2019)
Huanglongbing, the most destructive citrus disease worldwide, is caused by the bacterium ‘Candidatus Liberibacter asiaticus’ (CLas) and is vectored by the Asian citrus psyllid (ACP). Very little is known about the form and distribution of CLas in infected psyllids, especially at the ultrastructural level. Here, we examined these aspects by transmission electron microscopy, combined with immunogold labeling. In CLas-exposed ACP adults, the CLas bacterial cells were found to be pleomorphic taking tubular, spherical, or flask-shaped forms, some of which seemed to divide further. Small or large aggregates of CLas were found in vacuolated cytoplasmic pockets of most ACP organs and tissues examined, including the midgut, filter chamber, hindgut, Malpighian tubules, and secretory cells of the salivary glands, in addition to fat tissues, epidermis, muscle, hemocytes, neural tissues, bacteriome, and walls of the female spermatheca and oviduct. Large aggregates of CLas were found outside the midgut within the filter chamber and between the sublayers of the basal lamina of the hindgut and Malpighian tubules. Novel intracytoplasmic structures that we hypothesized as ‘putative CLas multiplication sites’ were found in the cells of the midgut, salivary glands, and other tissues in CLas-exposed ACP. These structures, characterized by containing a granular matrix and closely packed bacterial cells, were unbound by membranes and were frequently associated with rough endoplasmic reticulum. Our results point to the close association between CLas and its psyllid vector, and provide support for a circulative-propagative mode of transmission.